Evaluation of fractional exhaled nitric oxide in school-age children with asthma and sensitization to cat allergens - Kryvopustovа, Mariia (The Ukrainian Scientific Medical Youth Journal, 2022)
bronchial asthma is a chronic condition that is considerably prevalent among children. According to scientific evidence, cat allergens are most frequently responsible for the onset of asthma manifestations in children. Children are more likely to develop atopic asthma with eosinophilic inflammation. Under these circumstances, specific biomarkers are used as indicators of this inflammation. Fractional exhaled nitric oxide has been identified as a marker of eosinophilic airway inflammation in asthma. The aim of the research was to determine the fractional exhaled nitric oxide concentrations in school-age children with bronchial asthma and sensitization to cat allergens in order to predict asthma control status and assess therapeutic response. A total of 430 children aged between 6 and 17 years with asthma and sensitization to cat allergens participated in the study. The sensitization profile was investigated using a multicomponent molecular allergy diagnostic test (ALEX², Austria). The fractional exhaled nitric oxide levels were evaluated (NIOX VERO, Sweden). A total of 302 patients were enrolled in a retrospective study to find out how likely they were to gain bronchial asthma control over the course of therapy. As a result, a one-factor logistic regression analysis was conducted. A total of 128 children were included in the 12-month prospective research. All patients had a rise in fractional exhaled nitric oxide of > 20 ppb, with children with severe asthma having levels of 35 ppb or higher. The study discovered that changes in the fractional exhaled nitric oxide concentrations at the end of a three-month therapy could be linked to the maintenance of bronchial asthma control after a 12-month treatment period (r = 0.619; p <0.001). After a year of therapy, increasing baseline fractional exhaled nitric oxide levels reduced the probability of establishing bronchial asthma control in children (OR <1; p <0.001). The dynamics of fractional exhaled nitric oxide reduction increased the probability of achieving bronchial asthma control after completion of a three-month therapy (OR> 1; p <0.001). The effect of allergen-specific immunotherapy on the specified indicator of eosinophilic inflammation was demonstrated by a statistically significant difference in the mean values of fractional exhaled nitric oxide after a 12-month treatment period in the group of patients who received allergen-specific immunotherapy in combination with controller therapy versus the group of patients who received only controller therapy (p = 0.012). Thus, among school-age children with asthma and sensitization to cat allergens, the levels of fractional exhaled nitric oxide increased, especially in severe asthma. Not only the baseline fractional exhaled nitric oxide levels but also their dynamics after a three-month therapy should be considered when predicting the probability of establishing asthma control in these children. The inclusion of allergen-specific immunotherapy in the complex treatment of bronchial asthma in school-age children with sensitization to cat allergens has been shown to have a favourable therapeutic effect on the fractional exhaled nitric oxide levels.